(untitled) (Al-Qamar, 2022)
The existence of human life is based on the mixing and sharing of the two dominant emotions of happiness and sorrow. It is true that the scales of sorrow have always been heavier than the scales of happiness, but in spite of the lack of happiness and joy, man has always been struggling with difficulties and sufferings. The only thing that encourages man to survive in the nerve-wracking issues of human life is the feeling of happiness. And the three main means of expressing happiness are smile, laughter and Guffaw, whose existence is indispensable for human life. In the article under study, scribe has tried to explain these different manifestations of sense of humor under Western and Islamic concepts.